Design of a Simplified Histopathologic Model for Gastrointestinal Inflammation in Dogs. (September 2014) - Jergens, A. E.; Evans, R. B.; Ackermann, M.; Hostetter, J.; Willard, M.; Mansell, J.; Bilzer, T.; Wilcock, B.; Washabau, R.; Hall, E. J.; Minami, T.; Wang, C.; et al.
Significant interobserver variability in the diagnostic interpretation of endoscopic gastrointestinal (GI) specimens exists even with the use of World Small Animal Veterinary Association (WSAVA) standardization criteria. Chi-square analyses compared the extent of pathologists' agreement for microarchitectural features of inflammation in endoscopic specimens obtained from 253 animals of the original WSAVA study. Patterns of agreement between pathologists were classified as broad (3/4 pathologists agreed), dichotomous (2/4 pathologists agreed), or divergent (no agreement between pathologists). The simplified model for GI inflammation was based on those parameters for which the pathologists had either broad or minimally divergent opinions of histopathologic significance. In this model, the parameters chosen were as follows: gastric parameters (intraepithelial lymphocytes [IELs], lamina propria [LP] infiltrates, and mucosal fibrosis), duodenal parameters (villus atrophy, epithelial injury, IELs, crypt changes, and LP infiltrates), and colonic parameters (epithelial injury, crypt dilation, fibrosis, LP infiltrates, and goblet cell depletion). Preliminary data using this simplified model showed excellent correlation between pathologists in defining the presence and extent of GI inflammation in dogs.